Pelatihan Guru Dalam Kegiatan Pembuatan Rencana Pelaksanaan Pembelajaran (RPP) Merdeka Belajar di MI NU Raman Agung Kecamatan Buay Madang Timur - Imam Rodin; Dyah Pravitasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
This activity is motivated by the importance of understanding the making of a learning implementation plan. In fact, many teachers do not make lesson plans when they are going to carry out learning, this is because in making lesson plans must fulfill several very detailed components so that time in preparing the process of learning and evaluation activities is reduced. With the new regulation issued by the Ministry of Education and Culture regarding the